DESIGN OF A PACKED BIOREACTOR WITH IMMOBILIZED CELLS - Erazo E., Raymundo (2001)
A packed-bed bioreactor was designed with immobilized cells on a ceramic inert support (instalox seats). The design equatlons, considering an ideal plug-flow tubular bloreactor, were solved with appropiate algorithms installed in Mathcad 7P, obtaining a volume of 10L for the appropiate desing restrictions. It was determinad that for small bioreactors it is not necessary to consider the pattern of axial disperslon and that the isothermic operation is possible for the hlgh degree of retromixing of coolant in the jacket.